Pengaruh Motivasi, Lingkungan Kerja dan Mediasi Semangat Kerja Terhadap Kinerja Karyawan di Swalayan Metro Kampus Yogyakarta - Aprianto Patmanegara; Didik Subiyanto; Pristin Prima Sari (Widya Manajemen, 2021)
The purpose of this study was to determine the analysis of the influence of motivation, work environment, and work morale mediation on employee performance at Metro Kampus Yogyakarta. The sample in this study is part of the target population is 100 employees of Metro Yogyakarta Campus, where the sample is determined by the Slovin formula. The data was collected using a questionnaire or questionnaire collection method. The data analysis technique used is the regression technique which is supported by t-test and classical assumptions, the data that has been obtained are processed using SPSS 21. The results of this study indicate that motivation has a positive and significant effect on morale or performance in accordance with the significance test carried out by the test. -t and obtained tcount> ttable (6.089> 1.67722) and (2.987> 1.67722) with a = 0.05 so that Ho is rejected and Ha is accepted, the work environment has a positive and significant effect on morale or performance according to the significance test which was carried out by t-test and obtained tcount> ttable (4.273> 1.67722) and (2.037> 1.67722) with a = 0.05 so that Ho was rejected and Ha was accepted, morale had a positive and significant effect on performance in accordance with the test. The significance was carried out by t-test and obtained tcount> ttable (2.560> 1.67722) with a = 0.05 so that Ho was rejected and Ha was accepted.